Doxorubicin-Conjugated Mesoporous Magnetic Colloidal Nanocrystal Clusters Stabilized by Polysaccharide as a Smart Anticancer Drug Vehicle - Li, D.; Tang, J.; Chuan, W.; Guo, J.; Wang, S.; Chaudhary, Deeptangshu; Wang, C. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
Fabrication of magnetic nanocarriers that demonstrate enhanced biocompatibility and excellent colloidal stability is critical for the application of magnetic-motored drug delivery, and it remains a challenge. Herein, a novel approach to synthesize mesoporous magnetic colloidal nanocrystal clusters (MMCNCs) that are stabilized by agarose is described; these clusters demonstrate high magnetization, large surface area and pore volume, excellent colloidal stability, enhanced biocompatibility, and acid degradability. The hydroxyl groups of agarose, which cover the surface of the magnetic nanocrystals, are modified with vinyl groups, followed by click reaction with mercaptoacetyl hydrazine to form the terminal hydrazide (–CONHNH2). The anticancer agent doxorubicin (DOX) is then conjugated to MMCNCs through a hydrazone bond. The resulting hydrazone is acid cleavable, thereby providing a pH-sensitive drug release capability. This novel carrier provides an important step towards the construction of a new family of magnetic-motored drug-delivery systems. The experimental results show that the release rate of DOX from the DOX-conjugated MMCNCs (MMCNCs-DOX) is dramatically improved at low pH (tumor cell: pH 4–5 in the late stage of endolysosome and pH 5–6 from the early to late endosome), while almost no DOX is released at neutral pH (blood plasma). The cell cytotoxicity of the MMCNCs-DOX measured by MTT assay exhibits a comparable antitumor efficacy but lower cytotoxicity for normal cell lines, when measured against the free drug, thus achieving the aim of reducing side effects to normal tissues associated with controlled drug release.